Impact of mobility on COVID-19 spread – A time series analysis. (March 2022) - Zargari, Faraz; Aminpour, Nima; Ahmadian, Mohammad Amir; Samimi, Amir; Saidi, Saeid
Highlights: Studied and quantified the impact of mobility on COVID-19 spread. Supported with empirical data from Tehran. Performed time series analysis with public transit use and inter-city trips data. Investigated the impact of major events and holidays on virus spread. Discussed policy implications related to mobility for pandemic control. Abstract: In this paper, we investigate the impact of mobility on the spread of COVID-19 in Tehran, Iran. We have performed a time series analysis between the indicators of public transit use and inter-city trips on the number of infected people. Our results showed a significant relationship between the number of infected people and mobility variables with both short-term and long-term lags. The long-term effect of mobility showed to have a consistent lag correlation with the weekly number of new COVID-19 positive cases. In our statistical analysis, we also investigated key non-transportation variables. For instance, the mandatory use of masks in public transit resulted in observing a 10% decrease in the number of infected people. In addition, the results confirmed that super-spreading events had significant increases in the number of positive cases. We have also assessed the impact of major events and holidays throughout the study period and analyzed the impacts of mobility patterns in those situations. Our analysis shows that holidays without inter-city travel bans have been associated with a 27% increase in the number of weekly positive cases. As such, while holidays decrease transit usage, it can overall negatively affect spread control if proper control measures are not put in place. The result and discussions in this paper can help authorities understand the effects of different strategies and protocols with a pandemic control and choose the most beneficial ones.